The Effectiveness of Technology-Based Interventions for Reducing Loneliness in Older Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jin, Wenjing; Liu, Yihong; Yuan, Shulin; Bai, Ruhai; Li, Xuebin; Bai, Zhenggang (Frontiers in Psychology, 2021)
Objective: To systematically analyze the effectiveness of technology-based interventions for reducing loneliness in older adults. Methods: We searched relevant electronic databases from inception to April 2021, which included Cochrane Library, PubMed, Web of Science, SpringerLink, EMBASE, CNKI, and Wanfang. The following criteria were used: (i) study design— randomized controlled trial (RCT) designs, (ii) people —older adults (aged≥60 years), (iii) intervention— technology-based interventions in which a core component involved the use of technology to reduce loneliness in older adults; and (iv) outcome— reduction of loneliness level in terms of rating scale scores. Two reviewers independently identified eligible studies, extracted data, and assessed the risk of bias in the included studies. A third reviewer resolved any conflicts. The Cochrane Collaboration's bias assessment tool was used to evaluate the risk of bias for the included studies, and Review Manager 5.4 software was used for the meta-analysis. A random effects model was adopted to measure estimates of loneliness reduction, and standard mean differences (SMD) with a 95% confidence interval (CI) were calculated for each intervention-control contrast, and the I2 statistic was applied to examine heterogeneity. Results: A total of 391 participants from six RCTs were included in the review. Of these, three studies were rated as low-quality, and the remaining three were rated as moderate-quality studies. The meta-analysis showed that the evidence regarding the effects on loneliness of technology-based interventions compared with control groups was uncertain, and suggested that technology-based interventions resulted in little to no difference in loneliness reduction compared to control groups (SMD=-0.08, 95% CI −0.33 to 0.17, p=0.53). Two types of technology-based interventions were identified: smartphone-based video calls and computer-based training with Internet usage. The subgroup analysis found low-quality evidence to support the effectiveness of both intervention types (SMD=-0.01, 95% CI -0.25 to 0.24, p=0.95, and SMD=-0.38, 95% CI -0.19, 0.64, p=0.47, respectively). Conclusions: We found that evidence addressing the effectiveness of technology-based interventions for reducing loneliness in older adults is limited and very uncertain. This suggests that more research is needed to investigate the effects of technology-based interventions on loneliness in older adults.